Comunicación y discurso: análisis crítico del discurso en el consenso de la prensa ecuatoriana durante el referéndum y la consulta popular de 2018 - Lalangui Campoverde, Edison Cristóbal (2020)
The objective of this work is to analyze the factors that made possible the discursive consensus between the Ecuadorian press and the Government of Lenín Moreno, regarding the Referendum and the Popular Consultation of 2018. In this sense, the news, editorials and articles are taken as reference opinion that the newspapers El Comercio and El Telégrafo published during the election campaign. Simultaneously, the critical discourse analysis (ACD) is proposed as a theoretical and methodological tool, in order to problematize the discursive strategies that the press uses to legitimize certain political actors. For data processing, the NVivo 11 program of the QSR International organization is used. Finally, it shows how the two newspapers associate the figure of Rafael Correa with a past that Ecuadorians want to forget, and then support the content of the questions proposed by the Executive and boost the advantages of voting "Yes"